Impact of COVID-19 on pediatric asthma-related healthcare utilization in New York City: a community-based study - Erin Thanik; Kaoru Harada; Elizabeth Garland; Moira Bixby; Jasmine Bhatia; Ray Lopez; Sergio Galvez; Elan Dayanov; Krishna Vemuri; Douglas Bush; Nicholas B. DeFelice (BMC Pediatrics, 2023)
Abstract Background COVID-19 disproportionately affects families of low socioeconomic status and may worsen health disparities that existed prior to the pandemic. Asthma is a common chronic disease in children exacerbated by environmental exposures. Methods A cross-sectional survey was conducted to understand the impact of the initial stage of the pandemic on environmental and social conditions, along with access to care for children with asthma in New York City (NYC). Participants were recruited from a community-based organization in East Harlem and a nearby academic Pediatric Pulmonary clinic and categorized as having either public or private insurance (n = 51). Results Factors significantly associated with public compared to private insurance respectively were: increased reports of indoor asthma triggers (cockroach 76% vs 23%; mold 40% vs 12%), reduced income (72% vs 27%), and housing insecurity (32% vs 0%). Participants with public insurance were more likely to experience conditions less conducive to social distancing compared to respondents with private insurance, such as remaining in NYC (92% vs 38%) and using public transportation (44% vs 4%); families with private insurance also had greater access to remote work (81% vs 8%). Families with public insurance were significantly more likely to test positive for SARS-CoV-2 (48% vs 15%) but less likely to have gotten tested (76% vs 100%). Families with public insurance also reported greater challenges accessing office medical care and less access to telehealth, although not statistically significant (44% vs 19%; 68% vs 85%, respectively). Conclusions Findings highlight disproportionate burdens of the pandemic, and how these disparities affect children with asthma in urban environments.